Antimicrobial Resistant Escherichia coli Distribution along the Lower Part of the Chao Phraya River, Thailand - Rawiwan Sweattatut (2022)
Currently, antimicrobial drugs are not eliminated during the wastewater treatment process, especially in developing countries where antimicrobial drugs are used with less controls. An increase in contamination from effluent entering river systems is a major contributor to antimicrobial drug resistance and the spread of antimicrobial-resistant genes throughout rivers. This study aims to investigate the occurrence of antimicrobial-resistant Escherichia coli (E. coli) and evaluate the impact of urbanization on the distribution of antimicrobial-resistant E. coli along the lower part of the Chao Phraya River in Thailand. It was found that the geometric mean E. coli concentration was 624 CFU/100 mL. In addition, the geometric mean concentrations of E. coli resistant to cefotaxime and ciprofloxacin were 86 and 182 CFU/ 100 mL, respectively. A positive correlation coefficient was found between the concentration of antimicrobial-resistant E. coli and the number of population. The concentrations of E. coli were significantly positively correlated with antimicrobial-resistant E. coli (R = 0.950, P < 0.001). Therefore, this study indicated that antimicrobial-resistant E. coli were widely distributed in the Chao Phraya River with the highest concentrations in the Bangkok metropolitan area. These populations have been linked to an increase in antimicrobial-resistant E. coli contamination.